Revision of genus Zele Curtis (Hymenoptera, Braconidae, Euphorinae) from China, with description of nineteen new species - Yu Fang; Cornelis van Achterberg; Pu Tang; Xue-xin Chen (ZooKeys)
Zele Curtis is a braconid parasitoid wasp genus within the subfamily Euphorinae (Hymenoptera, Braconidae), consisting of only 30 species worldwide. The Chinese species of the genus Zele are revised and 29 species are now recognised, including 19 species new to science: Z. aquilus Fang, van Achterberg & Chen, sp. nov., Z. carinatus Fang, van Achterberg & Chen, sp. nov., Z. confusus Fang, van Achterberg & Chen, sp. nov., Z. cristatus Fang, van Achterberg & Chen, sp. nov., Z. curvatus Fang, van Achterberg & Chen, sp. nov., Z. curvinervis Fang, van Achterberg & Chen, sp. nov., Z. densipunctatus Fang, van Achterberg & Chen, sp. nov., Z. extensus Fang, van Achterberg & Chen, sp. nov., Z. fulgidus Fang, van Achterberg & Chen, sp. nov., Z. fuscatus Fang, van Achterberg & Chen, sp. nov., Z. impolitus Fang, van Achterberg & Chen, sp. nov., Z. inclinator Fang, van Achterberg & Chen, sp. nov., Z. irregularis Fang, van Achterberg & Chen, sp. nov., Z. petiolatus Fang, van Achterberg & Chen, sp. nov., Z. rugulosus Fang, van Achterberg & Chen, sp. nov., Z. sculpticoxis Fang, van Achterberg & Chen, sp. nov., Z. shaanxiensis Fang, van Achterberg & Chen, sp. nov., Z. syntomus Fang, van Achterberg & Chen, sp. nov., and Z. vacatus Fang, van Achterberg & Chen, sp. nov. 31 barcode region sequences of mitochondrial cytochrome c oxidase I (COI) from the genus Zele were obtained and combined with 102 sequences from BOLD. They were used to validate new species and to get an indication of similarity among species. Three species are reinstated: Zele peronatus (Shestakov, 1940), Z. romani (Fahringer, 1929), and Z. rufulus (Thomson, 1895). In addition, an identification key for the Zele species recorded in China (plus one expected species) is provided.